2018
DOI: 10.1177/0022022118814687
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Moral Virtue: When the Moral Transgressions of In-Group Members Are Judged More Severely

Abstract: Literature indicates that people tend to judge the moral transgressions committed by out-group members more severely than those of in-group members. However, these transgressions often conflate a moral transgression with some form of intergroup harm. There is little research examining in-group versus out-group transgressions of harmless offenses, which violate moral standards that bind people together (binding foundations). As these moral standards center around group cohesiveness, a transgression committed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(54 reference statements)
2
11
1
Order By: Relevance
“…Researchers should look into this question in the future. In addition, it should also be noted that while we mainly investigated the ingroup derogation phenomenon among mainland Chinese participants, the current findings are not directly applicable to the ingroup derogation found in minority groups (e.g., Allport, 1958; Jost et al, 2002; Livingston, 2002; Rudman et al, 2002; Ashburn-Nardo et al, 2003; Umphress et al, 2008; March and Graham, 2015; Axt et al, 2018) or to the ingroup derogation found against deviant ingroup members (Marques et al, 1988; Kunstman et al, 2016; Bettache et al, 2019). Although the theory of behavioral immune system may offer the ultimate explanation for the black sheep effect, explaining the ingroup derogation found in socially disadvantaged groups would be another story (e.g., Wu et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Researchers should look into this question in the future. In addition, it should also be noted that while we mainly investigated the ingroup derogation phenomenon among mainland Chinese participants, the current findings are not directly applicable to the ingroup derogation found in minority groups (e.g., Allport, 1958; Jost et al, 2002; Livingston, 2002; Rudman et al, 2002; Ashburn-Nardo et al, 2003; Umphress et al, 2008; March and Graham, 2015; Axt et al, 2018) or to the ingroup derogation found against deviant ingroup members (Marques et al, 1988; Kunstman et al, 2016; Bettache et al, 2019). Although the theory of behavioral immune system may offer the ultimate explanation for the black sheep effect, explaining the ingroup derogation found in socially disadvantaged groups would be another story (e.g., Wu et al, 2015, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…In previous studies (e.g., Jost et al, 2002; Ashburn-Nardo et al, 2003; Zhao et al, 2012; Liu et al, 2015; March and Graham, 2015; Bettache et al, 2019), researchers mainly investigated the ingroup derogation phenomenon among actual social groups. With three behavioral experiments, the present study investigated the bias of ingroup derogation by using the minimal group paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological dispositions related to political ideology may also extend to our sense of morality: The moral “senses” of fairness and care are more acute among the political left, whereas authority, loyalty, and sanctity are more acute on the political and religious right (Bettache, Hamamura, Amrani Idrissi, Amenyogbo, & Chiu, ; Graham, Haidt, & Nosek, ). Psychological traits that correlate with political ideology can be divided into epistemic and existential “motives” (Jost, ).…”
Section: Overview Of Present Researchmentioning
confidence: 99%